The impact of a carbon tax on economic growth and carbon dioxide emissions in Ireland - Thomas Conefrey; John D. Fitz Gerald; Laura Malaguzzi Valeri; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2008)
This paper analyses the medium-term effects of a carbon tax on growth and CO2 emissions in Ireland, a small open economy. We find that a double dividend exists if the carbon tax revenue is recycled through reduced income taxes. If the revenue is recycled by giving a lump-sum transfer to households, a double dividend is unlikely. We also determine that a greater incidence of the carbon tax falls on capital than on labour. When combined with a decrease in income tax, there is a clear shift of the tax burden from labour to capital. Finally, most of the effect on the economy is due to changes in the competitiveness of the manufacturing and market services sectors. These results hold even if we allow changes in energy prices to have an enhanced (detrimental) effect on Ireland's competitiveness.
Keywords: H23; Q54; 330; carbon tax; Ireland; double dividend; tax incidence; Ökosteuer; Kohlenstoff; Wirtschaftswachstum; Einkommensteuerpolitik; Öffentlicher Transfer; Doppelte Dividende; Kleines-offenes-Land; Irland